The Virginia Colony - Fradin, Dennis B. (Chicago : Childrens Press, 1986)
Presents the history, economy, culture, and people of the Virginia colony from the early Indian settlements to the Revolution. Includes brief biographies of prominent Virginians of the period from Powhatan to Thomas Jefferson and Henry Lee.
Includes index.
Bibliography: p. 153-154.
Keywords: Virginia -- History -- Juvenile literature. -- Revolution, 1775-1783; Virginia -- History -- Colonial period, ca. 1600-1775.; Virginia -- History -- Revolution, 1775-1783.; Virginia -- History -- Juvenile literature. -- Colonial period, ca. 1600-1775